State policy of Republic of Kazakhstan in the sphere of providing political stability (Journal of Philosophy Culture and Political Science, 2019)
In the article the author considers that the political stability is essential and important for all the countries of the world. Nowadays it isone of the actual problems as well. The author points out that there is no state strategic development without internal political stability. That iswhy to save its internal political stability and unitarity any state should be groupped around the common ideology. Saving the internal politicalstability is the state strategic direction of the multinational and multiconfessional Kazakhstan. Kazakhstan developed its model of saving thestate political stability and suggests it to all the countries of the world.